Perlindungan Hukum Terhadap Tenaga Kerja Dan Pengusaha Dalam Menjalankan Perusahaan Studi pada PT. Lajuperdana Indah Unit Pabrik Gula Pakis Baru - Aliqoh, siti Anik, Shalman Al-Farizy, S.H., M.Kn, IbuNuswardhani, S.H., S.U (2016)
Protection against labor law intended to ensure the rights of workers, to obtain the right of workers to do the obligation, before making the rights and obligations of workers and companies to perform mutual agreement with rights and obligations, if the obligation is not done then it must be responsible. This study aims to determine the process of bargaining between employers and workers and company rules that apply in the company PT. Lajuperdana Indah Pakis Baru Unit sugar factory, to determine the rights and obligations of the parties to the employment agreement, and to know the process for settling disputes within the company. The research method using empirical juridical approach with descriptive research because it reveals a systematic and comprehensive information regarding the legal protection for workers in the company. The results showed that prior to the agreement, workers must meet the requirements set by the company, after fulfilling each party to perform mutual agreement, the agreement occurs due to an agreement between workers and the company, after the agreement there arose as a result of the law, workers' rights is the obligation of the company, the company's rights is an obligation of the worker, if it is not implemented its obligations must be responsible and indemnify.